Effects of freeze-drying on cytology, ultrastructure, DNA fragmentation, and fertilizing ability of bovine sperm - Martins, Carlos Frederico (2007)
Freeze-drying sperm is an alternative to cryopreservation. Although sperm from various species has been freeze-dried, there are few reports for bovine sperm. The primary objective of this study was to evaluate the protective effect of various freeze-drying media on the structural and functional components of bovine sperm. The media tested were composed of TCM 199 with Hanks salts supplemented with 10% fetal calf serum (FCS) and TCM 199 with Hanks salts supplemented with 10% FCS and 0.2 M trehalose and EGTA solution. The efficiency of each medium on the preservation of freeze-dried sperm structures was evaluated with conventional and electron microscopy, DNA integrity was analyzed by a TUNEL assay, and fertilizing ability of lyophilized sperm was determined with ICSI. Although the plasma membrane was damaged in all media tested, mitochondria were similarly preserved in all freeze-drying treatments. The acrosome was best preserved in the media that contained trehalose (other treatments also conserved this structure). In contrast, media containing EGTA or trehalose most effectively preserved the nuclei in freeze-dried sperm, with only 2 and 5%, respectively, of cells with fragmented DNA. Furthermore, sperm conserved with these media also had higher (P < 0.05) rates of sperm head decondensation (32.5 and 27.5%), pronucleus formation (37.5 and 45.0%) and blastocyst formation (19.4 and 18.3%) than medium supplemented with FCS (15.0, 20.0 and 10.2%, respectively). In conclusion, media with EGTA and trehalose adequately protected bovine sperm during freeze-drying by preserving the viability of their nuclei.